-7n(-3n-5)=

Simple and best practice solution for -7n(-3n-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7n(-3n-5)= equation:


Simplifying
-7n(-3n + -5) = 0

Reorder the terms:
-7n(-5 + -3n) = 0
(-5 * -7n + -3n * -7n) = 0
(35n + 21n2) = 0

Solving
35n + 21n2 = 0

Solving for variable 'n'.

Factor out the Greatest Common Factor (GCF), '7n'.
7n(5 + 3n) = 0

Ignore the factor 7.

Subproblem 1

Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing n to the left, all other terms to the right. Simplifying n = 0

Subproblem 2

Set the factor '(5 + 3n)' equal to zero and attempt to solve: Simplifying 5 + 3n = 0 Solving 5 + 3n = 0 Move all terms containing n to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3n = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 3n = 0 + -5 3n = 0 + -5 Combine like terms: 0 + -5 = -5 3n = -5 Divide each side by '3'. n = -1.666666667 Simplifying n = -1.666666667

Solution

n = {0, -1.666666667}

See similar equations:

| (-3-4i)/(-8-9i) | | -(c-4)=8 | | 100m= | | 6x^2+0x-18=0 | | 30+15+0.35x=35+0.45x | | 4m-4-8=-2m | | 8(3s+3)=72 | | 5x^2+0x-9=0 | | 5(2l+2)=80 | | 30+15+0.35x=40 | | 2(n-1)-4(n+3)=8 | | 2x+2y-3z=-5 | | 3a^2+13a=-12 | | -12=4(y+5) | | 7t+3t=4+55-19 | | x - 4y + 3z = 10 | | xsquare+3x-4=6 | | 3-3=10m-4m | | v/8-3.1 | | 3+b=-20-8 | | 15x-12y=48 | | T/4-3t/4=16-9 | | -5b+2a=c | | 10-8x-5x+6= | | 5.9x-5=20 | | 2/5p1/2 | | (4+i)(x-y)=1-i | | 5/7-3y=2 | | (-15)(x/2.5)(1/2)=3x | | 3(3a-1)=30 | | 4x^2-8x=-24 | | -5(2b+3)+(11b-4)=0 |

Equations solver categories